FAKTOR-FAKTOR YANG MEMPENGARUHI DIVIDEND PAYOUT RATIO (DPR) PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA PERIODE 2014-2016 - Yuni Mirati, 14.05.52.0228; Srimindarti, Ceacilia (Students' Journal of Accounting and Banking, 2018)
This study aimed to examines debt to total asset, return on asset, debt to equity ratio, growth and firm size company to dividend payout ratio on manufacturing companies listed in indonesia stock exchange in the period 2014-2016. The population of this research are manufacturing companies listed in indonesia stock exchange. The sampling method using purposive sampling with the study period of 2014 until 2016 and obtained as many as 165 companies. The technique of data analysis is used multiple regression analysis. The results of this study shows that growth has a negative influence on dividend payout ratio. Firm size has a positive influence on dividend payout ratio. However, debt to total asset, return on asset, and debt to equity ratio has a not effect on dividend payout ratio.Keywords : Debt to Total Asset, Return On Asset, Debt to Equity Ratio, Growth, Firm Size dan Dividend Payout Ratio